Analisis Kepuasan Mahasiswa Terhadap Pelayanan Laboratorium Jaringan Menggunakan Pendekatan Importance-Performance Analysis - Syukhri Syukhri (invotek, 2018)
This study aims to analyze student satisfaction with the Network Laboratory services of the Electronics Engineering Department, Faculty of Engineering, Universitas Negeri Padang using the Importance Performance Analysis (IPA) approach and as an evaluation material in maximizing learning objectives, especially for networking subjects. The sampling technique uses simple random sampling, with research data sources covering 75 respondents students of Informatics Engineering Education program, Department of Electronics Engineering Faculty of Engineering, Universitas Negeri Padang class 2015. Data analysis in the form of validity and reliability tests using SPSS version 17.0. This research resulted in the quality of services received by students not as expected. Attributes that enter into quadrant I are attributes that need to be improved with top priority. These attributes are the conditions of a comfortable laboratory room, good internet access, good hardware quality, laboratory technician friendliness, ease of students in obtaining services, the presence of laboratory technicians, and the ease of laboratory technicians to be contacted. For this reason, a significant increase in these attributes is needed. With the analysis of student satisfaction on the Network Laboratory of the Electronics Engineering Department, Faculty of Engineering, Universitas Negeri Padang, it is expected that improvements can be made with priority attributes in quadrant I.